Crosslinking of the NER damage recognition proteins XPC-HR23B, XPA and RPA to photoreactive probes that mimic DNA damages - Maltseva, Ekaterina A.; Rechkunova, Nadejda I.; Gillet, Ludovic C.; Petruseva, Irina O.; Schärer, Orlando D.; Lavrik, Olga I. (Biochimica et biophysica acta, 2007)
A new assay to probe the mechanism of mammalian nucleotide excision repair (NER) was developed. Photoreactive arylazido analogues of dNMP in DNA were shown to be substrates for the human NER system. Oligonucleotides carrying photoreactive “damages” were prepared using the multi-stage protocol including one-nucleotide gap filling by DNA polymerase β using photoreactive dCTP or dUTP analogues followed by ligation of the resulting nick. Photoreactive 60-mers were annealed with single-stranded pBluescript II SK (+) and subsequently primer extension reactions were performed. Incubation of HeLa extracts with the plasmids containing photoreactive moieties resulted in an excision pattern typical of NER. DNA duplexes containing photoreactive analogues were used to analyze the interaction of XPC-HR23B, RPA, and XPA with damaged DNA using the photocrosslinking assay. Crosslinking of the XPC-HR23B complex with photoreactive 60-mers resulted in modification of its XPC subunit. RPA crosslinked to ssDNA or mismatched dsDNA more efficiently than to dsDNA, whereas XPA did not show a preference for any of the DNA species. XPC and XPA photocrosslinking to DNA decreased in the presence of Mg 2+ whereas RPA crosslinking to DNA was not sensitive to this cofactor. Our data establish a photocrosslinking assay for the investigation of the damage recognition step in human nucleotide excision repair.